2018
DOI: 10.1074/jbc.ra117.001558
|View full text |Cite
|
Sign up to set email alerts
|

Oxysterol-binding protein–related protein 5 (ORP5) promotes cell proliferation by activation of mTORC1 signaling

Abstract: Oxysterol-binding protein (OSBP) and OSBPrelated proteins (ORPs) constitute a large family of proteins that mainly function in lipid transport and sensing. ORP5 is an endoplasmic reticulum (ER)-anchored protein implicated in lipid transfer at the contact sites between the ER and other membranes. Recent studies indicate that ORP5 is also involved in cancer cell invasion and tumor progression. However, the molecular mechanism underlying ORP5's involvement in cancer is unclear. Here, we report that ORP5 promotes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…Accumulation of mitochondrial Ca 2+ has been shown to be involved in both 510 apoptotic cell death and senescence (permanent cell proliferation arrest) (Wiel,511 Lallet-Daher et al, 2014). Interestingly, it also has been shown that ORP5 expression 512 promotes cell proliferation (Du, Zadoorian et al, 2018). As our data show a new role 513 of ORP5 in regulating Ca 2+ import to mitochondria at ER-mitochondria contact sites 514 ( Fig.…”
Section: Orp5 Knockdown Induces Cell Senescence In a Sam50-dependent supporting
confidence: 52%
“…Accumulation of mitochondrial Ca 2+ has been shown to be involved in both 510 apoptotic cell death and senescence (permanent cell proliferation arrest) (Wiel,511 Lallet-Daher et al, 2014). Interestingly, it also has been shown that ORP5 expression 512 promotes cell proliferation (Du, Zadoorian et al, 2018). As our data show a new role 513 of ORP5 in regulating Ca 2+ import to mitochondria at ER-mitochondria contact sites 514 ( Fig.…”
Section: Orp5 Knockdown Induces Cell Senescence In a Sam50-dependent supporting
confidence: 52%
“…5, I-K). In contrast, ORP5 mutants deficient for PS (L389D) transport or PI(4)P/PI(4,5)P 2 binding (H478A/H479A; Chung et al, 2015;de Saint-Jean et al, 2011;Du et al, 2018;Galmes et al, 2016;Ghai et al, 2017;Maeda et al, 2013;Sohn et al, 2018) failed to reduce the size of LDs in ORP5 KO cells (Fig. 5, L and M), although L389D mutant seemed to have reduced the sizes of the LD population with a diameter >2 µm ( Fig.…”
Section: Orp5 Regulates Ld Sizementioning
confidence: 92%
“…Mechanistically, ORP5 was found to interact with NPC1 on late endosomes/lysosomes and transfer cholesterol to the ER and diminished ORP5 expression resulted in the accumulation of cholesterol in these late endocytic organelles (15). It was subsequently discovered that the ORP5 ORD is also able to interact with mammalian target of rapamycin (mTOR) on late endosomes/lysosomes, suggesting that ORP5 and cholesterol may play a role in nutrient sensing at the ER-late endosomal/lysosomal MCS (87). Together, ORP5 appears to function at several MCS and possess an array of lipid binding/transfer activities.…”
Section: Osbp Related Proteins Regulate Cell Adhesion and Migrationmentioning
confidence: 99%